Remote teaching and gamification: Use of the PhET Simulator in chemistry teaching - Oliveira, Eric Fabiano Sartorato de; Guatura, Janaina Aparecida; França, Maria Silvia Almeida de Souza; Nunes, Ursula Caroline Comodo de Melo; Romão, Estaner Claro (Seven Editora, 2023)
This article focuses on the use of the PhET Simulator, during Remote Teaching, as a learning strategy in the gamification of Chemistry teaching. Due to the COVID-19 scenario and the students’ difficulty in apprehending content related to the Periodic Table, the use of this Simulator was proposed and is justified by the interactivity between 47 students from the 9th grade of Elementary School. This is a quantitative-qualitative action research and the main objective was to show that remote work combined with gamification enabled the development of socio-emotional skills and skills related to the context of Chemistry using the Simulator as a playful and motivating tool. DOI:https://doi.org/10.56238/sevened2023.006-087